A common mechanism for evolution of single shear bands in large-strain deformation of metals. Issue 36 (22nd December 2018) - Sagapuram, Dinakar; Viswanathan, Koushik; Trumble, Kevin P.; Chandrasekar, Srinivasan
ABSTRACT: Shear banding, a type of inhomogeneous plastic flow involving very large local strains, occurs in a variety of material systems. We study dynamics of evolution of single shear bands at strain rates of up to per second in three different polycrystalline metal systems, using a special shear deformation framework and a micro-marker technique calibrated to track localised deformation fields at micrometer resolution. Once a band is nucleated as a weak interface, localised plastic flow occurs via Bingham-type viscous sliding between material segments on either side of the interface. As a result, the evolution and magnitude of strains and material displacements in the band vicinity are well-described by a model based on momentum diffusion. The viscosity at the band interface is very small, only a few mPa·sec, and is comparable to those of liquid metals at their melting point. Based on analysis of various contributions to band viscosity at the microscopic level, a plausible explanation based on phonon drag on dislocation motion is presented for the small viscosity. The accuracy of predictions made by the momentum diffusion model for different materials and deformation rates suggests that once nucleated, a shear band evolves by a common mechanism that is relatively insensitive to microstructure details.